Re-Actualization of the Concept of Al-Maslahah Al-Mursalah in Sharia-Based Public Policy Formulation - Aulia Rahmawati; Bagus Satrio (PT. Berkah Smart Academica, 2024)
This article explores the re-actualization of the Islamic legal concept of al-Maslahah al-Mursalah (public interest) in the context of formulating sharia-based public policies. The study aims to examine how al-Maslahah al-Mursalah can be utilized to address contemporary challenges and promote the welfare of society within a framework of Islamic principles. The methodology involves a comprehensive literature review of Islamic legal theory, particularly the principles of maqasid al-Sharia (objectives of Islamic law) and the application of al-Maslahah al-Mursalah. The research analyzes the potential of this concept in various policy domains, including economic development, social justice, and environmental sustainability. The findings highlight the importance of contextualizing Islamic legal principles to meet the evolving needs of society, while preserving the core values of justice, fairness, and the common good. The study concludes by advocating for the integration of al-Maslahah al-Mursalah in policy-making processes to ensure that public policies are both ethically sound and practically effective.